MARGINALISASI PEREMPUAN DALAM FILM GOWOK: KAMANSUTRA JAWA - Friskila Eby Suryani Imanuel; Moch. Muarifin; Nur Lailiyah (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the forms of women's marginalization and the impact of marginalization experienced by the female character in the film Gowok: Kamasutra Jawa by Hanung Bramantyo. This study uses a qualitative approach with a descriptive research type. The data sources consist of dialogues and scenes in the film that represent the marginalization of women. Data collection was carried out using observation and note-taking techniques, while data analysis used content analysis through the stages of data reduction, data presentation, and drawing conclusions. The results show that women's marginalization in the film is represented through subordination, stereotypes, violence, and the double burden experienced by the character Ratri. This marginalization is evident through the restriction of women's social space, the imposition of negative stigma, and the placement of women’s bodies as objects for fulfilling men’s interests within the gowok tradition. In addition to affecting social conditions, marginalization also has psychological impacts in the form of trauma, low self-esteem, and identity crisis. Nevertheless, this study finds that women who experience marginalization still have the opportunity to become agents of change if they receive social support and access to education. The film Gowok: Kamasutra Jawa not only represents gender injustice in patriarchal culture but also offers a critique of traditions that normalize marginalization.